Vaccination coverage estimates and utilization patterns of inactivated enterovirus 71 vaccine post vaccine introduction in Ningbo, China - Lixia Ye; Jieping Chen; Ting Fang; Rui Ma; Jianmei Wang; Xingqiang Pan; Hongjun Dong; Guozhang Xu (BMC, 2021)
Abstract Background In China, enterovirus 71 (EV71) is the major etiological agents of hand foot mouth disease that poses severe risks to children's health. Since 2015, three inactivated EV71 vaccines have been approved for use. Previous studies indicated the high willingness of EV71 vaccination in eastern China. However, few studies have assessed coverage and utilization patterns of EV71 vaccine in China. Methods Children born during 2012-2018 were sampled and their records were abstracted from Ningbo childhood immunization information management system. Descriptive statistics characterized the study population and assessed coverage and timeliness for EV71 vaccination. Simultaneous administration patterns as well as type of EV71 vaccine used were also evaluated. Bivariate and multivariable analysis was used to examine the relationship of socio-demographic characteristics with vaccination coverage and timeliness. Results Of 716,178 children living in Ningbo. One hundred seventy-two thousand two hundred thirty-six received EV71 vaccine with a coverage rate of 24.05% and only 8.61% received vaccination timely. 21.97% of children received the complete two dose EV71 series but only 6.49% completed timely. Vaccination coverage and timeliness increased significantly from 2012 birth cohort to 2018 birth cohort. Relatively higher coverage and timeliness were observed in resident children, Inner districts, high socioeconomic areas and large-scaled immunization clinics. Of 329,569 doses of EV71 vaccine, only 5853(1.78%) doses were administered at the same day as other vaccines. Conclusions There is a need for increasing EV71 vaccination coverage and timeliness as well as eliminating disparities among different populations. Our study highlights the importance of simultaneous administration to increasing coverage and timeliness of EV71 vaccination.